ANALYSIS OF STUDENTS’ ATTITUDES TOWARD STEM BASED-ON GENDER AND GRADE LEVEL: A COMPARATIVE STUDY BETWEEN INDONESIA AND THAILAND - Indit Vaiqoh; Supurwoko Supurwoko; Nurma Yunita Indriyanti (EDUSAINS, 2021)
ANALISIS SIKAP SISWA TERHADAP STEM BERDASARKAN GENDER DAN TINGKATAN KELAS: STUDI KOMPARASI INDONESIA DAN THAILANDAbstractAttitude is a tendency to behave and react to a given stimulus. The smoothness of STEM learning involves students, one of which is students' attitude towards STEM. Students at the junior high school level are a transitional period from children to adolescents who are not yet considered adulthood. Besides that, there is behavior stereotypical in male and female students during learning. This research was conducted to analyze students' attitudes towards Science, Technology, Engineering, and Mathematics (STEM) in Indonesia and Thailand in terms of grade level and gender. The research method used is descriptive quantitative using a survey. This study used the STEM questionnaire distributed to 139 students in Thailand and 90 students in Indonesia. Data were collected using a questionnaire about students' attitudes towards STEM and interview protocols for science teachers. Analysis of student attitudes, which focused on self-confidence, enjoyment, interest, and anxiety, showed that these attitudes were more dominant among students at the highest grade level in both countries. However, there is no significant difference between the attitudes of male and female students in Indonesia and Thailand; both are the same in responding to STEM learning.AbstrakSikap merupakan kecenderungan berperilaku dan reaksi terhadap stimulus yang diberikan. Kelancaran pembelajaran STEM yang melibatkan siswa, salah satunya adalah sikap siswa terhadap STEM. Siswa pada jenjang sekolah menengah pertama merupakan masa peralihan dari anak-anak menuju remaja yang belum dikatakan masa dewasa, selain itu adanya perilaku stereotype pada siswa laki-laki dan perempuan pada saat pembelajaran. Penelitian ini dilakukan untuk menganalisis sikap siswa terhadap Sains, Teknologi, Rekayasa, dan Matematika (STEM) di Indonesia dan Thailand ditinjau dari tingkat kelas dan jenis kelamin. Metode penelitian yang digunakan adalah kuantitatif deskriptif dengan menggunakan survei berupa kuesioner. Penelitian ini menggunakan kuesioner STEM yang dibagikan kepada 139 siswa di Thailand dan 90 siswa di Indonesia. Data dikumpulkan dengan menggunakan kuesioner tentang sikap siswa terhadap STEM dan protokol wawancara untuk guru IPA. Analisis sikap siswa yang berfokus pada kepercayaan diri, kesenangan, minat, dan kecemasan, menunjukkan bahwa sikap tersebut lebih dominan di antara siswa pada tingkat kelas tertinggi di kedua negara. Namun tidak ada perbedaan yang signifikan antara sikap siswa laki-laki dan perempuan di Indonesia dan Thailand, keduanya sama dalam merespon pembelajaran STEM.